2022
DOI: 10.21512/humaniora.v13i2.7680
|View full text |Cite
|
Sign up to set email alerts
|

Defining the Sense of Place Components in the Food and Craft Market at the World Heritage Site

Abstract: The research aimed to strengthen the future sense of place by focusing on the sense of place components, namely, physical, social, personal, and shared meaning aspects, as input to local stakeholders. The sense of place of Borobudur Temple stimulated visitors to attend the tourism area at the heritage site, whose potential could be strengthened by promoting the local creative economy and its identity. The research provided theoretical benefits as a basis for further research and practical benefits as input for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Meanwhile, from a non-physical point of view, there is the loading and unloading activities in the riverbank area each lasted from the past until now. Kusumowidagdo, et. al.…”
Section: A Review Of Literaturementioning
confidence: 99%
“…Meanwhile, from a non-physical point of view, there is the loading and unloading activities in the riverbank area each lasted from the past until now. Kusumowidagdo, et. al.…”
Section: A Review Of Literaturementioning
confidence: 99%
“…The physical environment has the ability to evoke emotions, create attachments, and influence behavior (Mei, Hågensen, & Kristiansen, 2018). Previous studies have shown that an integration of physical characteristics, activities, and meanings influences a sense of place and character (Kusumowidagdo et al, 2022). The physical forms and activities in a place significantly contribute to the development of place identity (Kusumowidagdo et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that an integration of physical characteristics, activities, and meanings influences a sense of place and character (Kusumowidagdo et al, 2022). The physical forms and activities in a place significantly contribute to the development of place identity (Kusumowidagdo et al, 2022). Social factors play a significant role in shaping a sense of place, while social environment, including community dynamics, social interactions, and cultural values, influences how individuals perceive and connect with a particular place (Erkılıç, Özmen, & Taştan, 2021;Najafi & Shariff, 2011).…”
Section: Introductionmentioning
confidence: 99%